Usefulness to Investors and Creditors of Information Provided by Financial Reporting: A Review of Empirical Accounting Research. - Sharp, Robert F. (The Accounting Review, 1983)
Abstract Reviews the book "Usefulness to Investors and Creditors of Information Provided by Financial Reporting: A Review of Empirical Accounting Research," by Paul A. Griffin.